Stress urinary incontinence: A case-based discussion - Carr, Lesley; Corcos, Jacques (Canadian Urological Association Journal, 2012)
At the conclusion of the sessions on stress urinary incontinence (SUI) in women, participants at the 2012 Canadian Urology Forum (academic and clinical urologists from across Canada) engaged in a discussion of optimal SUI evaluation and management. The discussion was led by Dr. Lesley Carr and co-facilitated by the other members of the Forum’s steering committee and was based on a patient case. This review provides a summary of the case and the discussion it generated.